2020
DOI: 10.7554/elife.59554
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific genomics and cross-species functional analysis implicate LRP2 in hypoplastic left heart syndrome

Abstract: Congenital heart diseases (CHDs), including hypoplastic left heart syndrome (HLHS), are genetically complex and poorly understood. Here, a multi-disciplinary platform was established to functionally evaluate novel CHD gene candidates, based on whole genome and iPSC RNA sequencing of a HLHS family-trio. Filtering for rare variants and altered expression in proband iPSCs prioritized 10 candidates. siRNA/RNAi-mediated knockdown in generic human iPSC-derived cardiomyocytes (hiPSC-CM) and in developing Drosophila a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 85 publications
(119 reference statements)
2
35
0
Order By: Relevance
“…The proportion of differentiated cell types was assessed nine days after siRNA treatment, a timepoint when active KD is no longer expected [9]. Efficiency of siRNA KD following transfection is expected to be maintained even when siRNAs against 3 different gene targets are combined, as demonstrated in previous experiments [7, 9].…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of differentiated cell types was assessed nine days after siRNA treatment, a timepoint when active KD is no longer expected [9]. Efficiency of siRNA KD following transfection is expected to be maintained even when siRNAs against 3 different gene targets are combined, as demonstrated in previous experiments [7, 9].…”
Section: Resultsmentioning
confidence: 99%
“…this observation was corroborated by the finding that the most significantly enriched GO subcellular locations included transcription factor complex (p-value < 1E-06, odds ratio = 3.14) and nuclear chromatin (p-value < 1E-06, odds ratio = 2.82), and among the molecular functions (Supplemental Data File S6), DNA-binding transcription activator activity, RNA polymerase II-specific (p-value < 1E-14, odds ratio = 3.33) and transcription coactivator activity (p-value < 1E-14, odds ratio = 3.38). Motivated by the enrichment of transcriptional regulatory processes in our interactome and several previous studies suggesting transcriptomic changes associated with HLHS [17,52,53], we further investigated the overlap of the HLHS interactome with four HLHS-related transcriptomic datasets. We studied whether the genes in the HLHS interactome were differentially expressed or alternatively spliced in four different RNAseq datasets comprising either tissues or cardiomyocytes derived from induced pluripotent stem cells (iPSCs) (Supplemental Data File S9).…”
Section: Go Biological Process Enrichment and Overlap With Hlhs Transcriptome Datasetsmentioning
confidence: 99%
“…Genome sequencing studies and genome-wide screening by comparative genomic hybridization have identified HLHS-associated variants in cardiomyopathy-associated genes such as MYBPC3, RYR2 and MYH6 [15], genes associated with mechanotransduction in cardiomyocytes such as VASP and TLN2 [16]. Other genes implicated in HLHS included RBFOX2 which mediates RNA metabolism [19], the cardiac transcription factor PROX1 [20], the endocytic receptor LRP2 [17] and the transcriptional regulator POGZ found in patients with HLHS and developmental delay [21]. However, despite the recovery of genes associated with HLHS, an integrative approach to elucidate their functional consequences is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Its full knockout leads to PTA in mice, and occasionally in humans, by exhausting the pool of OFT myocardial progenitors through premature differentiation [ 78 ]. However, compound heterozygous LRP2 missense variants have also been associated with hypoplastic left heart syndrome in humans [ 79 ], implying that other factors also mediate lateralized SHF contributions to the myocardial base of the truncal arteries.…”
Section: Embryonic Origins Of the Oftmentioning
confidence: 99%